Measuring the efficiency of working capital and its effect in Strengthen Profitability of communication companies - Ahmed Hussien Ahmed (Iraqi Journal for Administrative Sciences, 2024)
This study dealt with an important topic in financial thought, which is working capital and its impact on profitability. The main objective of the study mechanism is to analyze and measure the working capital and profitability indicators, as well as to know the correlations between the indicators of the two variables. The problem of this study stems from the fundamental question: Is there a trace of investment management in working capital to achieve profitability?. The spatial boundaries of the study community were a comprehensive survey of the telecommunications sector listed on the Iraq Stock Exchange, which included two companies, Asiacell Communications and Khatem Telecom. While the time limits of the study included a time series spanning eight years for the period 2011-2018, On the financial analysis side, three percentages were used to measure the working capital indicators (independent variable), namely the ratio of circulation, the percentage of total working capital and the percentage of net working capital, while three indicators were also used to measure profitability (dependent variable) this Rate of return on assets, the rate of return on equity, and rate of return on sales, A number of statistical methods were used to measure the relationships between the indicators of the arithmetic mean variables, simple correlation coefficient (r), test (t), simple regression coefficient (b), test (F) and coefficient of determination (R2). The most important conclusions reached by the study that there is no correlation and effect of statistically significant significance between the variables of the study and this confirms and supports the validity of the two hypotheses of the study.